2007
DOI: 10.4049/jimmunol.178.1.416
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Leukocyte Degranulation by cGMP-Dependent Protein Kinase and Phosphoinositide 3-Kinase: Potential Roles in Phosphorylation of Target Membrane SNARE Complex Proteins in Rat Mast Cells

Abstract: We examined the roles of cGMP-dependent protein kinase (PKG) and PI3K in degranulation induced by fMLF and by FcεRI cross-linking. In rat basophilic leukemia-2H3 cells expressing formyl peptide receptor, the PKG inhibitors KT5823 and Rp-8-Br-PET-cGMP, as well as the PI3K inhibitor LY294002, reduced agonist-stimulated β-hexosaminidase release in a dose-dependent manner. These inhibitors also abolished vesicular fusion with the plasma membrane, as evidenced by diminished annexin V staining. Agonist-induced degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 79 publications
3
39
0
Order By: Relevance
“…These results are consistent with the report that insulin stimulates secretion of ATP from dense granule via the NOcGMP-PKG pathway (49) and with the findings that the NOcGMP-PKG pathway stimulates exocytosis in leukocytes and neuronal cells (21)(22)(23). The cGMP-dependent granule secretion is associated with the PKG-dependent association between syntaxin 2 VAMP3 (vesicle-associated membrane protein 3) (49) in platelets and phosphorylation of soluble SNAP (N-ethylmaleimide-sensitive factor-attached protein)-23, and syntaxins 2 and 4 in leukocytes (21). However, the stimulatory effect cGMP in platelet activation was not repeated by some studies (50,51).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with the report that insulin stimulates secretion of ATP from dense granule via the NOcGMP-PKG pathway (49) and with the findings that the NOcGMP-PKG pathway stimulates exocytosis in leukocytes and neuronal cells (21)(22)(23). The cGMP-dependent granule secretion is associated with the PKG-dependent association between syntaxin 2 VAMP3 (vesicle-associated membrane protein 3) (49) in platelets and phosphorylation of soluble SNAP (N-ethylmaleimide-sensitive factor-attached protein)-23, and syntaxins 2 and 4 in leukocytes (21). However, the stimulatory effect cGMP in platelet activation was not repeated by some studies (50,51).…”
Section: Discussionsupporting
confidence: 82%
“…We have recently discovered that platelet granule secretion can be stimulated via the phosphoinositide 3-kinase (PI3K)-Akt-nitric oxide (NO)-cGMP pathway (16 -20). It has also been shown that granule secretion in leukocytes and neuronal cells can also be stimulated via the NO-cGMP pathway (21)(22)(23).…”
mentioning
confidence: 99%
“…In fact, exogenous expression of FPR1 or C5aR in a rat basophilic leukemia cell line renders these cells capable of releasing β-hexosaminidase upon stimulation, demonstrates the sufficiency of these receptors to trigger degranulation [25] . Simultaneous activation of several signaling pathways is required for degranulation [26] . As with other secretory cells, fusion of intracellular granules or vesicles in phagocytes requires calcium influx, which is triggered by GPCR signaling ( Figure 1).…”
Section: Chemotaxismentioning
confidence: 99%
“…23 Antibody detection of phosphorylated p47 phox was conducted as detailed in a recent publication. 28 The Western blot result was quantified with the use of ImageJ software (National Institutes of Health).…”
Section: Detection Of P47 Phox Phosphorylationmentioning
confidence: 99%
“…Taking advantage of this feature, Servant et al 22 used the PH domain of Akt as a probe to detect chemoattractant signaling in polarized neutrophils. The PI3K/Akt signaling pathway is one of the key components for the induced release of neutrophil granule contents, 23 although the exact mechanisms remain unknown. Akt is one of the protein kinases that phosphorylate p47 phox , resulting in its membrane translocation and activation of phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase.…”
Section: Introductionmentioning
confidence: 99%